REACTION OF WHEAT CULTIVARS TO FUSARIUM CROWN AND ROOT ROT UNDER FIELD CONDITION AT DUHOK-KURDISTAN REGION, IRAQ - S. AL-TOVI , BAREEN S.; HALEEM, RAED A. (Journal of Duhok University, 2020)
Field trial was conducted at College of Agricultural Engineering Sciences, University of Duhok, to evaluate the susceptibility of six wheat cultivars, three from durum wheat (Simeto, Doma and Sardar) and three from soft wheat (Cham 6 ,Adana 99 and Tamoz 2) to the Fusarium crown and root rot diseases. Two most common Fusarium species (F. graminearum, F. oxysporum) were used for this experiment. Inoculated plants produced symptoms of root rotting and scurfy, reddish brown to white discoloration of the crown area. The most susceptible cultivar was Doma since disease severity reached (0.33) and Sardar (0.29) whereas, the less susceptible one was Adana99 (0.16). F. graminearum caused a significant disease severity (0.41) compared to (0.32) resulted by F. oxysporum on all tested wheat cultivars, and subsequently caused comparable reduction of all tested criteria. However no completely resistant cultivar for disease was reported in this study, F. graminearum and F. oxysporum recorded the lowest infection on Adana99 cv.. Percentage of reduction in number of tillers was more in Doma, it was the most cultivar susceptible to F. oxysporium and F. graminearum with no significant difference at 48.14% and 45.2% respectively, while the less susceptible one to both fungi was Adana99 at 4.32% and 5.05% tiller reduction successively. F. graminearum showed more reduction in plant yield and the highest cultivar affected was Doma while the lowest one was Adana99.